Anatomic segment oriented hepatic resection in the management of colorectal metastases of the liver - Karamarković Aleksandar R.; Stefanović Branislav; Đukić Vladimir R.; Mihailović Vojin; Popović Nada (Srpski Arhiv za Celokupno Lekarstvo, 2003)
The prime role of hepatic resection in the management of colorectal cancer metastatic to the liver is firmly established. At least a third of patients who undergo liver resection for colorectal metastases can expect to survive five years. Since 1999, 106 hepatic metastases were resected in 42 patients (synchr. 8, metachr. 34, pts). We performed 12 monosegmentectomies (S2-S8), 4 bisegmentectomies (S4b, S5 and S5, S6), 6 sectorectomies (right posterior, left paramedian, left lateral), 3 polysegmentectomies (S4b, S5 S6), 8 billateral sectionectomies (S2, S3 and S6,S7) and in 9 cases multiple segmentectomies. In 4 cases initially unresectable colorectal metastases were downstaged by transcatheter HAI regional chemotherapy (Implantofix) and after that successfully resected. We favour vascular inflow occlusion through selective division of appropriate portal pedicle at the porta hepatis or by transparenchymal approach. Median blood loss was330±160 ml. The complication rate ammounted to 9.52% (bile fistula, abscess collection). No method related lethality occurred. During the follow-up period we registered tumor recurrence rate of 19.1% (8 pts), of which two patients were subjected to liver re-resection. Overall 3-year survival rate (Kaplan-Meier) is 38.9%. Multivariate analysis shows a significant correlation between 3-year survival and solitary (p-0.031) and unilobar metastases (p-0.014).